A method for producing a duplex stainless steel and a duplex stainless steel
Patent Information
- Application Number
- CN202611114569.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-20
AI Technical Summary
如专利文献1至5等所公开的,近期针对L-PBF制造得到的双相不锈钢的研究引起了大量关注,由于L-PBF独特的高冷速,大量先析铁素体无法转变为奥氏体,快速冷却使得铁素体和奥氏体失去了合金设计的之初应有的两相平衡,经过高温热处理后,塑性虽显著上升,但是强度大幅下降,无法满足深海探索等领域的要求
[0024]本发明解决了传统成分的双相不锈钢的打印态中的奥氏体和铁素体两相失衡,以及热处理后双相不锈钢强度低的问题,获得了高强度双相不锈钢。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing duplex stainless steel and a duplex stainless steel product, belonging to the field of alloy manufacturing. Background Technology
[0002] Additive manufacturing (AM), also known as 3D printing, is an advanced technology for manufacturing components through a layer-by-layer deposition process. Its significant advantages lie in its ability to construct parts with highly complex geometries without relying on molds, while also enabling efficient material utilization. In the field of metal additive manufacturing, high-energy heat sources (such as lasers or electron beams) are typically used to melt metal powder raw materials to form a molten pool. This molten pool undergoes rapid solidification and solid-state phase transition reactions, achieving rapid part forming through the layer-by-layer deposition of materials. Currently, the widely used metal additive manufacturing technology is Laser Powder Bed Fusion (L-PBF). Its process principle is as follows: using a high-energy-density, small-spot laser beam, following the contour path generated by software slicing, rapidly scans a pre-laid metal powder bed. Through point-by-point, line-by-line, and surface-by-surface melting and deposition, the part is ultimately formed layer by layer.
[0003] Duplex stainless steel consists of two phases, ferrite and austenite, in a near 1:1 ratio. It combines the high strength of ferritic steel with the high toughness and weldability of austenitic stainless steel, making it widely used in petrochemicals, deep-sea construction, and other fields. Recent research on duplex stainless steel manufactured using L-PBF, as disclosed in patent documents 1 to 5, has attracted considerable attention. Due to the unique high cooling rate of L-PBF, a large amount of proprecipitated ferrite cannot transform into austenite. Rapid cooling causes the ferrite and austenite to lose the two-phase balance that should have been achieved in the initial alloy design. After high-temperature heat treatment, although the plasticity increases significantly, the strength decreases drastically, failing to meet the requirements of deep-sea exploration and other fields.
[0004] Existing technical documents
[0005] Patent Document 1: CN114107827A
[0006] Patent Document 2: CN115948698A
[0007] Patent Document 3: CN116197412A
[0008] Patent Document 4: CN116809954A
[0009] Patent Document 5: CN120243903A Summary of the Invention
[0010] The problem the invention aims to solve
[0011] To address the shortcomings of the existing technology, the present invention aims to provide a method for preparing duplex stainless steel and a duplex stainless steel product. The present invention obtains a high-strength, high-ductility duplex stainless steel through additive manufacturing and heat treatment, which meets the needs of fields such as deep-sea exploration.
[0012] Solution for solving the problem
[0013] Specifically, the present invention provides a method for preparing duplex stainless steel, which includes the following steps: (1) mixing duplex stainless steel master powder with Cr2N powder to obtain mixed powder; (2) forming the mixed powder by additive manufacturing to obtain printed stainless steel, i.e. printed duplex stainless steel; wherein, by mass percentage, the composition of the duplex stainless steel master powder is: C≤0.03%, Si≤0.8%, Cr: 20-27%, Ni: 3-6%, Mn: 0-3%, Mo: 2-4%, N: 0.08%-0.8%, with the balance being Fe and unavoidable impurities.
[0014] According to the preparation method of the present invention, it further includes step (3): heat-treating the printed stainless steel obtained in step (2) to obtain heat-treated stainless steel, that is, heat-treated duplex stainless steel.
[0015] According to the preparation method of the present invention, the mass ratio of duplex stainless steel master powder and Cr2N powder is 1:0.01-0.1.
[0016] According to the preparation method of the present invention, the particle size of the Cr2N powder is 2000~3000 mesh.
[0017] According to the preparation method of the present invention, the particle size of the duplex stainless steel master powder is 15-53 micrometers.
[0018] According to the preparation method of the present invention, the mixed powder is obtained by mechanically mixing duplex stainless steel master powder and Cr2N powder to obtain the mixed powder.
[0019] According to the preparation method of the present invention, the additive manufacturing is carried out by laser powder bed melting, wherein the laser power is 150-210W, the scanning speed is 600-1000mm / s, the laser scanning spacing is 50-60 micrometers, the thickness of each layer is 20-30 micrometers, and the interlayer rotation angle is 67-90°.
[0020] According to the preparation method of the present invention, the heat treatment is carried out as follows: the temperature is increased to 1100-1150°C at a rate of 5-10°C / min, held for 10-15 minutes, and then quenched in water to room temperature.
[0021] The present invention also provides a duplex stainless steel, which is obtained by the preparation method described in the present invention.
[0022] According to the present invention, the duplex stainless steel in the heat-treated state comprises an austenitic structure and a ferrite structure, wherein the volume fraction of austenite is 50-70% and the volume fraction of ferrite is 30-50%.
[0023] The effects of the invention
[0024] This invention solves the problems of austenite and ferrite phase imbalance in the printed state of traditional duplex stainless steel and low strength of duplex stainless steel after heat treatment, and obtains high-strength duplex stainless steel.
[0025] The duplex stainless steel of the present invention contains a uniform duplex structure, which makes the duplex stainless steel have high strength and good strength-plasticity matching. It solves the problems of existing duplex stainless steel having high strength but poor toughness in the printed state after additive manufacturing and insufficient strength in the heat-treated state. The preparation method is simple, reliable and safe, and meets the needs of deep-sea exploration and other fields. Attached Figure Description
[0026] Figure 1 Tensile property curve test charts of printed stainless steel-I (Example 1), heat-treated stainless steel-I (Example 2), and printed stainless steel-comparison I (Comparative Example 1) and heat-treated stainless steel-comparison I (Comparative Example 2).
[0027] Figure 2 The graph shows the EBSD test results of heat-treated stainless steel-I, with the scale bar at 50 μm. Detailed Implementation
[0028] Various exemplary embodiments, features, and aspects of the present invention will be described in detail below. The term "exemplary" as used herein means "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as superior to or better than other embodiments.
[0029] Furthermore, to better illustrate the present invention, numerous specific details are set forth in the following detailed embodiments. Those skilled in the art should understand that the present invention can be practiced without certain specific details. In other instances, methods, means, apparatus, and steps well known to those skilled in the art have not been described in detail in order to highlight the spirit of the present invention.
[0030] Unless otherwise stated, all units used in this specification are international standard units, and all numerical values and ranges appearing in this invention should be understood to include systematic errors that are unavoidable in industrial production.
[0031] In this specification, the word "may" has two meanings: to perform a certain process and not to perform a certain process.
[0032] In this specification, references to "some specific / preferred embodiments," "other specific / preferred embodiments," "implementation," etc., refer to specific elements (e.g., features, structures, properties, and / or characteristics) related to that embodiment, which are included in at least one of the embodiments described herein and may or may not be present in other embodiments. Furthermore, it should be understood that these elements may be combined in any suitable manner in various embodiments.
[0033] In this specification, the range of values referred to as "value A to value B" refers to the range including the endpoint values A and B.
[0034] In this instruction manual, "room temperature" refers to a temperature between 10°C and 40°C.
[0035] <Preparation Methods of Duplex Stainless Steel>
[0036] This invention provides a method for preparing duplex stainless steel, which includes the following steps:
[0037] (1) Mix duplex stainless steel master powder with Cr2N powder to obtain mixed powder; (2) Shape the mixed powder by additive manufacturing to obtain printed stainless steel, i.e. printed duplex stainless steel; wherein, by mass percentage, the composition of duplex stainless steel master powder is: C≤0.03%, Si≤0.8%, Cr: 20-27%, Ni: 3-6%, Mn: 0-3%, Mo: 2-4%, N: 0.08%-0.8%, with the balance being Fe and unavoidable impurities.
[0038] This invention introduces nitrogen into the matrix by using low-melting-point nitrides. At the same time, additive manufacturing technology has the characteristics of rapid melting and solidification, which can rapidly melt and solidify Cr2N, thereby preserving nitrogen in the matrix.
[0039] In some embodiments, the duplex stainless steel master powder of the present invention can be 2202 duplex stainless steel powder, 2205 duplex stainless steel powder or 2507 duplex stainless steel powder, wherein 2205 duplex stainless steel powder is preferred.
[0040] In some embodiments, the preparation method of the present invention further includes step (3): heat-treating the printed stainless steel obtained in step (2) to obtain heat-treated stainless steel, i.e. heat-treated duplex stainless steel.
[0041] By subjecting the printed duplex stainless steel to subsequent heat treatment, nitrogen diffusion is made uniform, thereby improving the strength and toughness of the duplex stainless steel of the present invention.
[0042] In some embodiments, the mass ratio of duplex stainless steel master powder to Cr2N powder in the preparation method of the present invention is 1:0.01-0.1.
[0043] Using the above mass ratio allows for controlled addition of nitrogen content.
[0044] In some implementations, the ratio of duplex stainless steel master powder to Cr2N powder can be 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, or 1:0.09.
[0045] In some embodiments, the Cr2N powder in the preparation method of the present invention has a particle size of 2000-3000 mesh. Adding Cr2N powder with the above-mentioned mesh size can avoid affecting the flowability of the powder used for additive manufacturing.
[0046] In some embodiments, the particle size of the duplex stainless steel master powder in the preparation method of the present invention is 15-53 micrometers. The particle size of the aforementioned duplex stainless steel master powder is suitable for use in laser selective melting processes.
[0047] In some embodiments, the mixed powder in the preparation method of the present invention is obtained by mechanically mixing duplex stainless steel master powder and Cr2N powder to obtain the mixed powder.
[0048] This invention achieves in-situ alloying by mechanically mixing duplex stainless steel master powder and Cr2N powder.
[0049] In some implementations, the mechanical method may include ultrasonic vibration or a ball milling mixture, with ultrasonic vibration being preferred.
[0050] In some implementations, the parameters of the ultrasonic vibration mode are an ultrasonic frequency of 50-60 Hz and a vibration time of 8-10 minutes.
[0051] Compared to other methods of obtaining mixed powders, such as gas atomization, this application can prepare high-nitrogen duplex steel powder using a low-cost and simple mixing method.
[0052] In some embodiments, the additive manufacturing process of the present invention is carried out by laser powder bed melting, wherein the laser power is 150-210W, the scanning speed is 600-1000mm / s, the laser scanning spacing is 50-60 micrometers, the thickness of each layer is 20-30 micrometers, and the interlayer rotation angle is 67-90°.
[0053] In some embodiments, the additive manufacturing atmosphere is an inert gas atmosphere, preferably an argon atmosphere.
[0054] In some embodiments, the heat treatment in the preparation method of the present invention is carried out as follows: the temperature is increased to 1100-1150°C at a rate of 5-10°C / min, held for 10-15 minutes, and then quenched in water to room temperature.
[0055] By performing the heat treatment as described above, uniform diffusion of nitrogen can be achieved between the components, and the phase ratio conforms to that of common duplex stainless steel.
[0056] <Duplex Stainless Steel>
[0057] The present invention also provides a duplex stainless steel, which is a duplex stainless steel obtained by the preparation method of the present invention.
[0058] In some implementations, the printed duplex stainless steel contains a ferritic structure with a volume fraction of 99%-100%.
[0059] In some embodiments, the heat-treated duplex stainless steel comprises an austenitic and a ferritic structure, wherein the volume fraction of austenite is 50-70% and the volume fraction of ferrite is 30-50%.
[0060] In some embodiments, the heat-treated duplex stainless steel comprises austenitic and ferritic structures, wherein the volume fraction of austenite is 64% and the volume fraction of ferrite is 36%, which is within the phase ratio range of common duplex stainless steels.
[0061] The duplex stainless steel in the printed state of this invention has a yield strength of 1238 MPa or higher, a tensile strength of 1336 MPa or higher, and an elongation after fracture of 6.7% or higher, exhibiting excellent properties. The duplex stainless steel in the heat-treated state has a yield strength of 794 MPa or higher, a tensile strength of 1020 MPa or higher, and an elongation after fracture of 42.4% or higher, also exhibiting excellent properties.
[0062] Example
[0063] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0064] The following describes the test conditions for the duplex stainless steel of the present invention.
[0065] Ingredient testing
[0066] The elemental content of duplex stainless steel was determined using an Agilent inductively coupled plasma mass spectrometer (ICP-MS) and a LECO ONH836 oxygen, nitrogen and hydrogen analyzer.
[0067] Organizational Characterization
[0068] The microstructure, grain orientation, grain boundary distribution, and texture characteristics of the samples in the examples and comparative examples were characterized and analyzed using a TESCAN MIRA series field emission scanning electron microscope with an electron backscatter diffraction (EBSD) system.
[0069] Mechanical property testing
[0070] A WANCE ETM105D microcomputer-controlled electronic universal testing machine was used to conduct static tensile mechanical property tests according to GB / T 228.1-2021 Metallic materials—Tensive testing—Part 1: Tests at room temperature. The tensile strength, yield strength, and total elongation after fracture of the samples were tested. All tensile specimens were designed and processed according to this national standard, and were uniformly cut using wire electrical discharge machining to ensure dimensional accuracy. The test adopted a constant strain rate control mode, with the tensile strain rate set at 1×10⁻⁶. -4 s.
[0071] The following describes the preparation process and the performance of the samples obtained in the embodiments of the present invention. The 2205 duplex stainless steel powder in the embodiments and comparative examples was purchased from Jinggao Youcai (Beijing) Technology Co., Ltd., and the Cr2N powder was purchased from Qinghe County Enyi Metal Materials Co., Ltd.
[0072] Example 1
[0073] 2205 duplex stainless steel powder was placed in a powder sieving machine to sieve particles ranging from 15 to 53 micrometers. The sieved 2205 duplex stainless steel powder and 2000-mesh Cr2N powder were placed in a container at a ratio of 1:0.03 and placed in an ultrasonic vibrator. The container was vibrated at 60 Hz for 10 minutes to ensure uniform mixing, resulting in a mixed powder. This mixed powder was then evenly spread in a powder hopper. A thin layer of 2205 duplex stainless steel powder was then deposited onto a substrate. Additive manufacturing was performed using an L-PBF metal printer with the following parameters: laser power of 200W, laser scanning speed of 800 mm / s, laser scanning spacing of 60 micrometers, layer thickness of 20 micrometers, and interlayer rotation angle of 67°. Argon gas was used in the printing atmosphere, and printing was performed at atmospheric pressure. The printed size was 12 × 60 × 12 mm. The obtained sample was designated as Printed Stainless Steel-I.
[0074] Example 2
[0075] Printed stainless steel was obtained in the same manner as in Example 1, and then subjected to heat treatment. The specific heat treatment process is as follows: the heat treatment furnace was heated to 1100°C at a rate of 10°C / min; the furnace door was opened, the sample was placed in, and after the temperature stabilized, it was held at that temperature for 10 minutes; then the sample was removed and water-quenched to room temperature. The obtained sample is designated as heat-treated stainless steel-I.
[0076] Comparative Example 1
[0077] The sample was obtained in the same manner as in Example 1, except that no Cr2N powder was added. The obtained sample was designated as Printed Stainless Steel - Comparative I.
[0078] Comparative Example 2
[0079] Printed stainless steel was obtained in the same manner as in Comparative Example 1, and the printed stainless steel was heat-treated in the same manner as in Example 2. The obtained sample is designated as heat-treated stainless steel - Comparative I.
[0080] Example 2 and Comparative Example 2 are heat-treated stainless steels obtained by heat-treating the printed stainless steel of Example 1 and Comparative Example 1, respectively. Since the two have similar compositions, the composition of the heat-treated stainless steels obtained in Example 2 and Comparative Example 2 was tested, and the results are shown in Table 1.
[0081] Table 1. Composition test results of duplex stainless steel
[0082]
[0083] The duplex stainless steels obtained in Examples 1 and 2 and Comparative Examples 1 and 2 were subjected to performance tests, specifically tensile strength, yield strength, and elongation after fracture. The results are shown in Table 2 and [Table data missing]. Figure 1 .
[0084] Table 2. Performance test results of duplex stainless steel
[0085]
[0086] As shown in Table 2, compared with the printed stainless steel - Comparison I, the printed stainless steel - I has higher tensile strength and yield strength, and better performance; compared with the heat-treated stainless steel - Comparison I, the heat-treated stainless steel - I has higher tensile strength and yield strength, and there is no significant difference in elongation after fracture, and its overall performance is excellent.
[0087] As shown in Table 1, adding Cr2N to duplex stainless steel powder during additive manufacturing increases the chromium and nitrogen content, which is beneficial to the corrosion resistance of duplex stainless steel. In Comparative Examples 1 and 2, where Cr2N was not added, the strength of the printed stainless steel (Comparative I) and the heat-treated stainless steel (Comparative I) was significantly worse, indicating that the addition of Cr2N is beneficial to improving the strength of duplex stainless steel.
[0088] The microstructure of heat-treated stainless steel-I was characterized by EBSD testing, and the results are as follows: Figure 2 As shown. Among them. Figure 2 (a) is the inverse pole diagram of heat-treated stainless steel-I, and no obvious defects can be found. Figure 2 (b) is a phase ratio diagram of heat-treated stainless steel-I, showing an austenite volume fraction of 64% and a ferrite volume fraction of 36%.
[0089] It should be noted that although the technical solution of the present invention has been described with specific examples, those skilled in the art will understand that the present invention should not be limited thereto.
[0090] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or technical improvements to the embodiments in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. A method for preparing duplex stainless steel, characterized in that, Includes the following steps: (1) Mix duplex stainless steel master powder with Cr2N powder to obtain a mixed powder. (2) The mixed powder is shaped by additive manufacturing to obtain printed stainless steel, that is, the printed duplex stainless steel; The composition of the duplex stainless steel master powder, by mass percentage, is: C≤0.03%, Si≤0.8%, Cr: 20-27%, Ni: 3-6%, Mn: 0-3%, Mo: 2-4%, N: 0.08%-0.8%, with the balance being Fe and unavoidable impurities.
2. The preparation method according to claim 1, characterized in that, The preparation method further includes step (3): heat-treating the printed stainless steel obtained in step (2) to obtain heat-treated stainless steel, that is, the heat-treated duplex stainless steel.
3. The preparation method according to claim 1 or 2, characterized in that, The mass ratio of the duplex stainless steel master powder to the Cr2N powder is 1:0.01-0.
1.
4. The preparation method according to claim 1 or 2, characterized in that, The particle size of the Cr2N powder is 2000~3000 mesh.
5. The preparation method according to claim 1 or 2, characterized in that, The particle size of the duplex stainless steel master powder is 15-53 micrometers.
6. The preparation method according to claim 1 or 2, characterized in that, The mixed powder is obtained by mechanically mixing the duplex stainless steel master powder and the Cr2N powder.
7. The preparation method according to claim 1 or 2, characterized in that, The additive manufacturing method is carried out by laser powder bed melting, wherein the laser power is 150-210W, the scanning speed is 600-1000mm / s, the laser scanning spacing is 50-60 micrometers, the thickness of each layer is 20-30 micrometers, and the interlayer rotation angle is 67-90°.
8. The preparation method according to claim 2, characterized in that, The heat treatment is carried out as follows: the temperature is increased to 1100-1150℃ at a rate of 5-10℃ / min, held for 10-15 minutes, and then quenched in water to room temperature.
9. A duplex stainless steel, characterized in that, It is a duplex stainless steel obtained by the preparation method according to any one of claims 1-8.
10. The duplex stainless steel according to claim 9, characterized in that, Duplex stainless steel in the heat-treated state contains austenitic and ferritic structures, with the volume fraction of austenite being 50-70% and the volume fraction of ferrite being 30-50%.
Citation Information
Patent Citations
Duplex stainless steel powder for 3D printing and preparation and printing method thereof
CN114107827A
Duplex stainless steel material and application thereof in preparation of seawater heat exchanger
CN115948698A
Method for improving plasticity of 3D printing duplex stainless steel
CN116197412A
Method for forming nano oxide reinforced duplex stainless steel through selective laser melting
CN116809954A
High-strength high-toughness corrosion-resistant super duplex stainless steel and preparation method thereof
CN120243903A